The impact of activity based working (ABW) on workplace activity, eating behaviours, productivity, and satisfaction - Arundell, L.; Sudholz, B.; Teychenne, M.; Salmon, J.; Hayward, B.; Healy, Genevieve; Timperio, A. (Molecular Diversity Preservation International (MDPI), 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. The redesign of the physical workplace according to activity-based working (ABW) principles has potential to influence employee health and workplace outcomes. This natural experiment examined changes in accelerometer-derived workplace activity, self-reported eating behaviours, productivity, workplace satisfaction before (March to November 2014) and six to nine months after moving to an ABW workplace compared to a comparison workplace (n = 146 at baseline (56% ABW, aged 40.1 ± 8.5 years, 72% female). Interviews were also conducted with 21 ABW participants. Between- and within-group differences were examined and mixed model analysis examined intervention effects over time. Effect sizes were calculated on change scores (Cohen’s d). Although not statistically significant, ABW participants had meaningful improvements in workday sedentary time, light-, and moderate-to-vigorous intensity physical activity, job satisfaction and relationship with co-workers (d = 0.379–0.577), and small declines in productivity (d = 0.278). There were significant, meaningful, and beneficial intervention effects on perceived organisational support for being active in the workplace, frequency of eating lunch with colleagues, and satisfaction with the physical environment in ABW compared to comparison participants (d = 0.501–0.839). Qualitative data suggested that ABW employees associated ABW with greater opportunities for movement and collaboration, but had mixed views on the impact on productivity. Future research with larger samples and over longer follow-up periods is warranted.